Management of existing conflicts in the school environment a state school in the city of Linhares-ES (Research, Society and Development, 2021)
A review of the relevant literature shows that conflict is an essential and unavoidable human phenomenon, because where there is human interaction there is a likelihood of personal likes and dislikes. These agreements and disagreements between individuals and groups at school sometimes lead to conflicts which in turn are neither constructive nor disruptive, but the way they are handled at school makes them positive or negative. Causes of conflict include differences in perception, limited resources, overlapping authority, among others; while conflict management strategies include accommodation, prevention, competition and collaboration. The aim of this article, which seeks to analyze the nature of conflicts existing in the school environment and the respective impacts, positive and negative, of these differences on the pedagogical structure of the school. Based on this discussion, the document suggests that there should be regular staff meetings, a good communication network and the code of conduct for teachers and students should be made available to all staff and students, in order to know their limits and avoid conflicts.